Application of GIS in public health in India: A literature-based review, analysis, and recommendations - Marilyn O'Hara Ruiz; Arun Kumar Sharma (Wolters Kluwer Medknow Publications, 2016)
The implementation of geospatial technologies and methods for improving health has become widespread in many nations, but India's adoption of these approaches has been fairly slow. With a large population, ongoing public health challenges, and a growing economy with an emphasis on innovative technologies, the adoption of spatial approaches to disease surveillance, spatial epidemiology, and implementation of health policies in India has great potential for both success and efficacy. Through our evaluation of scientific papers selected through a structured key phrase review of the National Center for Biotechnology Information on the database PubMed, we found that current spatial approaches to health research in India are fairly descriptive in nature, but the use of more complex models and statistics is increasing. The institutional home of the authors is skewed regionally, with Delhi and South India more likely to show evidence of use. The need for scientists engaged in spatial health analysis to first digitize basic data, such as maps of road networks, hydrological features, and land use, is a strong impediment to efficiency, and their work would certainly advance more quickly without this requirement.